(4Z)-4-[(2E)-1-Hydroxy-3-(3-nitrophenyl)prop-2-en-1-ylidene]-3-methyl-1-(4-methylphenyl)-1H-pyrazol-5(4H)-one - Chaudhry, Faryal (International Union of Crystallography, 2012)
In the title compound, C(20)H(17)N(3)O(4), the dihedral angles between the heterocyclic ring and the toluene and nitrobenzene rings are 4.21 (15) and 11.43 (14)°, respectively. The whole molecule is close to planar (r.m.s. deviation for the 27 non-H atoms = 0.171 Å). Two S(6) rings are formed due to intramolecular C—H⋯O and O—H⋯O hydrogen bonds. In the crystal, inversion dimers linked by pairs of C—H⋯O bonds generate R (2) (2)(10) loops and further C—H⋯O bonds link the dimers along the b-axis direction. There exist π–π interactions between the heterocyclic rings at a centroid–centroid distance of 3.7126 (10) Å and between the centroids of the benzene rings at a distance of 3.8710 (16) Å.